Desirable competencies when hiring outdoor pursuits trip leaders on university and college campuses - DeMers, Anna (My University, 2012)
Many universities offer outdoor pursuits trips (e.g., backpacking, canoeing) for their students. These trips include incoming student orientation programs, physical education and recreation classes, and extracurricular activities. The leaders who are leading these trips play a key role in making the trip a success (Shooter, Paisley, & Sibthorp, 2009a). Having the right staff to facilitate these trips is very important. There are many components that go into hiring competent people and training quality outdoor leaders (Teschner & Wolter, 1990). The overriding problem is a lack of knowledge of general standards regarding outdoor leaders in university programs. While there are agencies that accredit outdoor programs (e.g., Wilderness Education Association (WEA), Association for Experiential Education (AEE)), many university programs do not seek accreditation, but instead set their own criteria for leaders. This study examines how university programs, both academic and extracurricular, set standards for trip leaders. It identifies 1) minimum qualifications of leaders, 2) components of their leader training, and 3) competencies desired in the hiring process.
Keywords: Work -- Psychological aspects; Civil service -- Personnel management.; Human capital -- United States -- Planning.